Impact of industrial shut down and land use change in Chaliyar Basin, India - Shabeer, AM (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
This paper explains the impact of industrial shut down and land use change in Chaliyar river basin in Kerala, the southern state of India. The gradual migration of local labour for jobs abroad has made a remarkable impact on the land use in the local region. The large scale migration was chiefly the outcome of unemployment in the local region as a result of the shutdown of the rayon industry which was the only source of income to the local village community. Two parallel phenomena were observed since 2001: the migration pattern of labour force in the study area, and the changes in land use pattern. Given this background of the problem it is interesting to observe the land use changes through remote sensing during different time periods